2019
DOI: 10.1111/xen.12533
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐graft porcine‐specific CD4+FoxP3+ regulatory T cells by CD40‐CD154 blockade prevented the rejection of porcine islet graft in diabetic mice

Abstract: Background: Anti-CD154 monoclonal antibody (mAb) treatment has been known to have potential to induce immune tolerance in organ transplantation. Several studies have suggested the involvement of CD4 + regulatory T cells (T reg s) in xeno-immune tolerance. However, the characteristics of T reg s and the mechanisms of their regulatory functions in islet xenotransplantation have not been clearly defined. Method:Adult porcine islet cells were isolated and purified, and were transplanted under the kidney capsule of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The main highlight of this study was the early and continued presence of CD4 and CD8 Tregs within the NPSC grafts. CD4 Tregs have been implicated in prolongation of allograft survival and recently have been demonstrated to improve survival of xenografts 20 24 , 40 . Tregs have been shown to mediate immune tolerance and homeostasis by suppressing T effector cells, inhibiting cell–cell contact with APCs, and secreting regulatory cytokines 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main highlight of this study was the early and continued presence of CD4 and CD8 Tregs within the NPSC grafts. CD4 Tregs have been implicated in prolongation of allograft survival and recently have been demonstrated to improve survival of xenografts 20 24 , 40 . Tregs have been shown to mediate immune tolerance and homeostasis by suppressing T effector cells, inhibiting cell–cell contact with APCs, and secreting regulatory cytokines 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T cells (Tregs) have potential to suppress cell-mediated responses generated against xenogeneic tissue thus improving graft survival 19 21 . Use of CD40-CD154 blockade has led to long-term survival of porcine islet xenografts in diabetic mice 22 24 . Using a combination of anti-lymphocyte function associated antigen (LFA)-1 and anti-CD154 mAbs to prolong graft survival, Arefanian et al demonstrated that CD4 + Foxp3 + Tregs (CD4 Tregs) were responsible for this survival as CD4 Treg depletion resulted in graft rejection and reconstitution of B6 rag −/− mice with splenocytes from these tolerant mice resulted in prolonged porcine islet xenograft survival 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently observed in mice model that if CD4 + CD25 + regulatory T cells were depleted in the early phase of porcine islet xenotransplantation with CD40-CD154 axis blockade, grafts were not protected by the T cells. 40 It also implies that CD4 + /CD8 + ratios as a biomarker should be interpreted in this context.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous issue of Xenotransplantation, Perota et al reported that they had successfully generated a bovine double‐KO model lacking both αGal and Neu5Gc; Chen et al studied the specific role of TLR2 in xenograft rejection of porcine iliac endothelial cells; Yoon et al described the mechanism of how CD154 blockade protects islet xenografts from rejection; Bracey et al assessed the biocompatibility of porcine xenograft‐derived bone scaffold in vitro. Additionally, the abstracts from the International Xenotransplantation Association 2019 Congress are also published here and outline a number of novel projects that were presented at the congress.…”
Section: Introductionmentioning
confidence: 99%